Meticillin-resistant Staphylococcus aureus (MRSA) acquisition risk in an endemic neonatal intensive care unit with an active surveillance culture and decolonization programme. Issue 1 (January 2017) - Pierce, R.; Lessler, J.; Popoola, V.O.; Milstone, A.M.
Summary: Background: Meticillin-resistant Staphylococcus aureus (MRSA) is a leading cause of healthcare-associated infection in the neonatal intensive care unit (NICU). Decolonization may eliminate bacterial reservoirs that drive MRSA transmission. Aim: To measure the association between colonization pressure from decolonized and non-decolonized neonates and MRSA acquisition to inform use of this strategy for control of endemic MRSA. Methods: An eight-year retrospective cohort study was conducted in a level-4 NICU that used active surveillance cultures and decolonization for MRSA control. Weekly colonization pressure exposures were defined as the number of patient-days of concurrent admission with treated (decolonized) and untreated (non-decolonized) MRSA carriers in the preceding seven days. Poisson regression was used to estimate risk of incident MRSA colonization associated with colonization pressure exposures. The population-attributable fraction was calculated to assess the proportion of overall unit MRSA incidence attributable to treated or untreated patients in this setting. Findings: Every person-day increase in exposure to an untreated MRSA carrier was associated with a 6% increase in MRSA acquisition risk [relative risk (RR): 1.06; 95% confidence interval (CI): 1.01–1.11]. Risk of acquisition was not influenced by exposure to treated, isolated MRSA carriers (RR: 1.01; 95% CI: 0.98–1.04). In the context of this MRSA control programme, 22% (95% CI: 4.0–37) of MRSA acquisition could be attributed to exposures to untreated MRSA carriers. Conclusion: Untreated MRSA carriers were an important reservoir for transmission. Decolonized patients on contact isolation posed no detectable transmission threat, supporting the hypothesis that decolonization may reduce patient-to-patient transmission. Non-patient reservoirs may contribute to unit MRSA acquisition and require further investigation.